Profil Kemampuan Metakognisi Siswa Kelas XII SMA Negeri 1 Atambua dalam Pembelajaran Matematika - Israfil Israfil; Patrisius Afrisno Udil (Universitas Nusa Cendana, 2021)
Metacognitive ability is one of the important factors that affect students' mathematics learning achievement. This study investigated the profile of students' metacognitive ability. This study aimed to describe the level of students' metacognitive abilities in general and based on each aspect and indicators. The method of this research is descriptive quantitative by taking 1 class as sample from 4 classes population, with the sampling method used is random sampling. The instruments used in this research was Metacognitive Awareness Inventory (MAI) questionnaire. The results showed tha generally most of students have a good and good enough metacognition ability. It is also found that for each aspect most of students have good and good enough metacognition knowledge and metacognition skills. Meanwhile, based on its indicator for each aspect it is found that there were students with poor declarative knowledge (aspect of metacognition knowledge) and also there were students with poor evaluation skills (aspect of metacognition skills). For others indicators, it is found that students have good and good enough procedural knowledge, condisional knowledge, planning skills, and monitoring skills.Keywords: Metacognitive ability, metacognitive knowledge, metacognitive skills.